The heparan sulfate proteoglycan syndecan is an in vivo ligand for the Drosophila LAR receptor tyrosine phosphatase. - Fox, A.N.; Zinn, K. (Current Biology, 2005)
Receptor tyrosine phosphatases (RPTPs) are essential for axon guidance and synaptogenesis in Drosophila. Each guidance decision made by embryonic motor axons during outgrowth to their muscle targets requires a specific subset of the five neural RPTPs. The logic underlying these requirements, however, is still unclear, partially because the ligands recognized by RPTPs at growth cone choice points have not been identified. RPTPs in general are still "orphan receptors" because, while they have been found to interact in vitro with many different proteins, their in vivo ligands are unknown.Here we use a new type of deficiency screen to identify the transmembrane heparan sulfate proteoglycan Syndecan (Sdc) as a ligand for the neuronal RPTP LAR. LAR interacts with the glycosaminoglycan chains of Syndecan in vitro with nanomolar affinity. Genetic interaction studies using Sdc and Lar LOF mutations demonstrate that Sdc contributes to LAR's function in motor axon guidance. We also show that overexpression of Sdc on muscles generates the same phenotype as overexpression of LAR in neurons and that genetic removal of LAR suppresses the phenotype produced by ectopic muscle Sdc. Finally, we show that there is at least one additional, nonproteoglycan, ligand for LAR encoded in the genome.Taken together, our results demonstrate that Sdc on muscles can interact with neuronal LAR in vivo and that binding to Sdc increases LAR's signaling efficacy. Thus, Sdc is a ligand that can act in trans to positively regulate signal transduction through LAR within neuronal growth cones.